Pancreatology A Clinical Casebook - Gardner, Timothy B.; Smith, Kerrington D.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This clinical casebook provides a comprehensive yet concise state-of-the-art review of pancreatic disease. Presented in a case-based format, each case focuses on a different varient of pancreatic disease and pancreatic cancer, with sections on diagnosis and early detection, management of the disease, and treatment of complications from the disease. The role of neoadjuvant therapy for pancreatic cancer and emerging treatment algorithms for chronic pancreatitis are also highlighted in the text. Written by experts in the field, Pancreatology: A Clinical Casebook is a valuable resource for clinicians, surgeons, and researchers interested in caring for patients with pancreatic disease. .
Risk Factors for Acute and Chronic Pancreatitis -- Hereditary Pancreatitis -- Hospital Management of Acute Pancreatitis -- Acute Biliary Pancreatitis -- Classification and Management of Pancreatic Cysts -- Medical and Endoscopic Management of Chronic Pancreatitis -- Complications of Acute Pancreatitis -- Endoscopic Therapy for Complications of Acute Pancreatitis -- Autoimmune Pancreatitis -- Diagnosis of and Screening for Pancreatic Malignancy -- Hereditary Pancreatic Cancer -- Optimizing Nutrition for the Patient after Pancreaticoduodenectomy: Pancreatic Insufficiency -- Palliative Care and Pancreatic Disease -- Staging Diagnostic Laparoscopy for Localized Pancreatic Cancer -- Neoadjuvant Multimodality Therapy for Borderline Resectable Pancreatic Head Cancer -- Drainage and Resection Surgery for Pancreatitis -- Pancreatectomy with Islet Autotransplant. .
Keywords: Medicine; Gastroenterology; Hepatology; Medicine & Public Health; Gastroenterology; Hepatology